Characterizing temporal and spatial scales of radiatively driven convection in a deep, ice‐free lake. Issue 10 (3rd September 2022) - Austin, Jay; Hill, Craig; Fredrickson, Jacob; Weber, Grace; Weiss, Kaelan
Abstract: From May to July 2019, an array of moored equipment was deployed in Lake Superior to characterize the spatial and temporal scales of radiatively driven convection (RDC). Previous work suggested that convective plumes have horizontal scales on the order of tens of meters, posing a significant observational challenge. The centerpiece of the deployment was a large, two‐dimensional (2D) array of thermistors that provided resolution on the order of 10 meters in both the vertical and a single horizontal dimension. This was augmented by an acoustic Doppler current meter mooring and a meteorology buoy capable of estimating surface heat and momentum fluxes. Instantaneous temperature variability at a given location is dominated by a lateral background flow advecting strong horizontal temperature gradients. By combining velocity data with temperature data, this fact can be used to examine horizontal structure at centimeter scales, and can produce 2D images of instantaneous temperature distribution on a horizontal surface, revealing multiple patterns of temperature anomaly distribution. The walls of convective structures are very sharp, with horizontal gradients on the order of 1°C m −1 ; horizontal scales of convective structures themselves are on the order of many tens of meters. Finally, convection is shown to strongly control the vertical distribution of water quality parameters.